Development Method of the Doratask Method in Its Use in Runway Capacity Calculations - Atmaka, Ekky Widha (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Until now, Indonesia does not have its own method or a developed method for calculating runway capacity. The DORATASK method recommended by ICAO has the weakness that it can only be optimally used for single runway operations. Meanwhile, there are runway characters in Indonesia: Opposite Runway Operation, Crossing Runway Operation, Parallel Runway Operation, Staggered Parallel Runway Operation, and Low/Very Low Traffic for AFIS Airports. The aim of this research is to develop the DORATASK method so that it is compatible with runway capacity calculations with other characteristics. The method used in this research is mixed-method, with descriptive analysis categories and final results/research conclusions using ratio calculations/validity tests and formulas for new methods taken from main parameters, velocity and Pythagoras. The results of the validity test between the DORATASK method and the new method were obtained at the four airports, namely Soekarno Hatta Airport with the DORATASK method = 107 movements/hour and with the new method = 148 movements/hour, Budiarto Airport with the DORATASK method = 39 movements/hour and with the new method = 48 movements/hour, Ende Airport with the DORATASK method = 1 movement/hour and with the new method = 11 movements/hour, Rokot Airport with the DORATASK method = no results obtained and with the new method = 4 movements/hour. The principles and parameters used in the DORATASK method are still used, but are developed in the Aircraft mix, Runway Occupancy Time and Separation parameters.